RHETORICAL RELATIONS IN GERUND CLAUSES IN GOVERNMENT DECREES (PERcursos Linguísticos, 2022)
According to the Rhetorical Structure Theory (RST) (MANN; THOMPSON, 1987, 1988), the rhetorical nucleus-satellite relations do not presuppose a one-to-one correspondence between the main clause and the hypotactic clause. In terms of language use, this fact reflects patterns of clause combination in which hypotactic clauses in list relation constitute a satellite of a single nucleus. Considering such assumptions, this article proposes to analyze the rhetorical relations established by gerund clauses collected in the Governmental Decrees of Ceará state. Such structures were coded according to the following variables: (i) position concerning the nuclear, (ii) quantity and (iii) rhetorical relation. The results were associated with the principle of iconicity (GIVÓN, 2001). It was noticed that the 64 collected clauses revealed the gerund clauses are pre-verbal (100%), confirming the iconicity of the sequence and the fact that most Decrees have two of these clauses. Concerning rhetorical relations, we identified the multi-nuclear list and same-unit relations as well as the nucleus-satellite relations of elaboration, circumstance, background, preparation, and justification. Through the text analysis, we realized that the emerging relations are under the administrative act’s principle of motivation and they provide the reader to understand and accept the Decrees’ content.